A Hydrologically Fractured State? Nation-Building, the Hirakud Dam and Societal Divisions in Eastern India. Issue 3 (3rd May 2020) - Routray, Sailen; Oskarsson, Patrik; Satpathy, Puspanjali
Abstract: This article analyses how long-running, multilayered conflicts over water at the Hirakud dam underpin present-day societal divisions in Odisha state. There are four unresolved conflicts over this dam in the state: movements against displacement, movements for rehabilitation, struggles between agricultural and industrial water users, and, finally, disputes between federal states. These have generated societal ruptures from the announcement of the dam in 1946 to the present day. We argue that understanding the confluence and ingrained, overlapping character of these conflicts provide important vantage points for understanding the present uneasy constitution of subregional state fabrication in Odisha.